EFEKTIVITAS ECOPRINT SEBAGAI ECO-ART THERAPY UNTUK MENINGKATKAN KESEJAHTERAAN PSIKOLOGI GURU SEKOLAH LUAR BIASA - Uswatun Khasanah; Khofidotur Rofiah; Isrumila Isrumila; Ninik Hudahawanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the application of the Ecoprint method as part of Eco-Art Therapy in improving the psychological well-being of teachers in special schools. This research method combines a qualitative approach through interviews with a quantitative method through a quasi-experimental method. The sample was purposively selected, consisting of 30 teachers. The instruments used include the Maslach Burnout Inventory (MBI) and the Perceived Stress Scale (PSS).The results showed the highest score of Ecoprint 97, the lowest score 72 and the average 87. The level of effectiveness of the intervention reached 68.4, classified as moderately effective. This finding proves that Ecoprint as Eco-Art Therapy has a significant effect on improving the psychological well-being of special school teachers